Seals like it hot: Changes in surface temperature of harbour seals (Phoca vitulina) from late pregnancy to moult - Paterson, W; Sparling, C E; Thompson, D; Pomeroy, P P; Currie, John; McCafferty, D J (Journal of Thermal Biology, 2012)
The annual moult in harbour seals(Phoca vitulina L.) follows a few weeks after the end of lactation and is characterised by a progressive loss and regrowth of hair which is apparent over a 4–6 week period. It is thought that during the moult harbour seals increase the time spent ashore as an adaptation to avoid additional energy costs associated with blood flow to the skin surface. The aim of this study was to determine the extent to which harbour seals regulated their surface temperature in order to maximise hair growth during the moult. The surface temperatures of two female harbour seals were recorded incaptivity from late pregnancy to completion of the moult using infrared thermography. In this study, animals hauled out(exited the water onto land) more frequently during lactation and throughout the moult. Compared to the premoult period the temperature difference between body surface and air temperature(dT ) showed a 10 1C elevation at the peak of the moult. Also, during the moult (dT)reached a higher maximum at a faster rate over a two hour haul-out period. Heat loss was estimated to increase during the moult and was equivalent to an approximate doubling of resting metabolic rate. It was there fore evident that harbour seals minimise the energetic cost of the moult by hauling out so that they can maintain optimal high skin surface temperature for hair growth. Human disturbance athaul-out sites that causes animals to enter the water during the moult may have consequences for harbour seals for two reasons. Firstly, reduced time spent ashore in optimal conditions for hair regeneration may prolong the duration of the moult and secondly, repeatedly forcing animals into the water when their skin temperature is high will incur an energetic cost.